Some Results on the Optimal Depletion of Exhaustible Resources Under Negative Discounting - Mitra, Tapan (Review of Economic Studies, 1981)
Journal Article Some Results on the Optimal Depletion of Exhaustible Resources Under Negative Discounting Get access Tapan Mitra Tapan Mitra State University of New York, Stony Brook Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 3, July 1981, Pages 521–532, https://doi.org/10.2307/2297164 Published: 01 July 1981 Article history Received: 01 May 1977 Accepted: 01 October 1980 Published: 01 July 1981